Development of Basic Physics-Virtual Laboratory Teaching Module Based on Science Literacy - Maiyanti, Aziza Anggi; Nurlaili, Eva Alfi; Ridwan, Muhammad; Yusal, Yulianti (Department of Physics Education, Universitas Mataram, 2024)
This research aims to develop a basic physics teaching module with a virtual laboratory to improve students' science literacy in terms of attitudes. The results of PISA 2022 illustrate that the literacy skills possessed by students in Indonesia are still in a position that is not good enough, which means that the expectations of the competence of independent curriculum graduates are still far behind. Based on the results of research conducted by Hendri in 2019, data was obtained that out of 138 students at one of the universities in Indonesia, it is known that they have science literacy skills in the low category. Supported by the initial data obtained by researchers on Tadris Science students, a result of was also obtained in the low category. Science literacy ability can be seen through two aspects, namely attitude and cognitive attitudes. Based on the results of the validation test of the teaching module, a result of obtained with very valid criteria, which means that the basic physics teaching module developed is suitable for use for learning. The results of the implementation of the teaching module obtained the significance of the results of the pretest and posttest results of students' science literacy attitudes were obtained with a result that this basic physics teaching module is practically used to improve science literacy in terms of attitudes. This is in accordance with cognitive theory which states that students should be at the level of developing abstract thinking by enriching objects, phenomena and real experiences. This research reflects that technology has a huge influence on the learning process which has direct implications for learning outcomes in cognitive areas, scientific skills and attitude.